Sustentabilidade da avicultura de corte no estado de Goiás: uma análise sob a ótica da nova economia institucional - Santos, Willams Douglas dos (2023)
The production of chicken meat increased significantly over the past decades, influenced by technical gains in production, slaughter and processing along the poultry chain. In the Brazilian State of Goiás, specifically, production increased expressively too, favored by a highly technological agricultural-industrial system, the significant local supply of grains and the presence of economies of scale. It is in this context that the present study is developed, seeking to understand the sustainability actions carried out in the productive chain of poultry in the State of Goiás. For this, the theoretical assumptions and parameters of the New Institutional Economics were used as a methodological reference, in parallel with the categories of the SWOT Matrix. The data used involved the survey of secondary data from the four main agribusinesses in the State of Goiás. The importance of this research is justified by its contribution to the understanding of the current scenario of chicken meat production, as well as for the understanding of the strategies that are reflected in better sustainable practices in the chain. The results allowed us to conclude that this scenario has led to an increase in the supply of chicken meat, however, causing negative consequences to the environment. To circumvent such effects, the agribusinesses have sought to perform some actions, such as water treatment to return to rivers and springs, renewable energy practices, alternatives that minimize the use of natural resources and reduce the environmental impacts generated by the production of chicken meat.